2021
DOI: 10.1111/aos.14838
|View full text |Cite
|
Sign up to set email alerts
|

Silicone oil‐free syringes, siliconized syringes and needles: quantitative assessment of silicone oil release with drugs used for intravitreal injection

Abstract: Purpose: This study aimed to quantify the amount of silicone oil (SO) released across a variety of syringe and needle models routinely used for intravitreal injection. Methods: The release of SO was assessed in eight models of syringes, two of which were reported to be 'SO-free', and eleven models of needles with unknown SO content. To evaluate SO release within the context of anti-VEGF therapeutics, syringes were evaluated using aflibercept, bevacizumab, buffer, ziv-aflibercept and formulation buffer. All syr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The total amount of Si oil (~0.6–1.0 mg/mL) and its distribution in prefilled syringes can impact syringe functionality and particle formation [ 25 , 26 ]. The siliconized polypropylene insulin syringes showed significantly higher silicone oil particle counts than the prefilled glass syringes [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total amount of Si oil (~0.6–1.0 mg/mL) and its distribution in prefilled syringes can impact syringe functionality and particle formation [ 25 , 26 ]. The siliconized polypropylene insulin syringes showed significantly higher silicone oil particle counts than the prefilled glass syringes [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variations in the prevalence of droplets can be attributed to many other factors, such as the form of presentation, the repackaging, transport and manipulation of the drug, or even the examination technique. Recently, and by means of fluorescence labelling and imaging flow cytometry, micro-sized droplets (0.1–10 μm size range) have been detected in the vitreous of patients [ 5 ]. These cannot be detected by slit-lamp observation and recent literature point to its potential inflammatory power [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020 Olea et al conducted a study with silicone oil-free syringes and demonstrated absence of oil droplets larger than 25 μm [ 9 ]. Other authors, like Mello et al have found trace amounts of silicone oil released from purportedly silicone oil-free syringes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations